Current use of NT-proBNP in elderly patients and the impact of the selected threshold value: lessons from a big data analysis. (14th October 2021) - Meune, C; Goudot, F.X; Boukertouta, T; Lazureanu, A; Msadek, S; Chenevier-Gobeaux, C; Martins-Meune, E
Abstract: Background: Natriuretic peptides (NPs) are widely used in the diagnosis and risk stratification of heart failure (HF).NPs may have a reduced discriminative ability in the subgroup of elderly patients. Methods: We examined all biological tests performed from February 2010 to August 2015 in two districts in the French Brittany. We report the "real-world" use of N-terminal pro-B-type natriuretic peptide (NT-proBNP) in an elderly population and examine the measured concentration and potential impact of the cut-off value's selection. Results: From a total of 3, 606, 432 tests ordered in 557, 650 adult patients, 56, 653 included at least one NT-proBNP measurement. NT-proBNP measurements gradually increased by 10-y age categories up to 80–90 y, and 39, 828 (70.3%) of all measurements have been done in patients ≥75y. NT-proBNP concentrations increased with advanced age (Pearson's correlation coefficient: 0.2; p<10 –5 ), with concentrations of 3, 564±6, 440 ng/L in patients ≥75y. NT-proBNP was inversely correlated with creatinine clearance (p<10 –5 ). Respective proportions of NT-proBNP below the threshold value were 22.6% in patients aged 70 to 80y and less than 10% in those over 80 y when considering a single threshold value of 125 ng/L, and 31% and 33% in the same groups when considering a dual age-adjusted threshold value of 450 ng/L in patients >75y (p<0.001 for all comparisons). Conclusion: Among a very large cohort, we observed that NT-proBNP is increasingly measured in elderly patients. NT-proBNP concentrations increase with age, and the selection of the threshold value markedly impacts the proportion of "low" versus "high" results. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Roche Diagnostics